Perencanaan Pewadahan Dan Tata Letak TPS Limbah B3 Restoran Dan Tempat Hiburan - Pratama Putri, Esha Nurrahmania; Rachmanto, Tuhu Agung (Universitas Gajah Putih, 2023)
At present, restaurants and entertainment venues are places that are growing very rapidly in big cities. From business/production activities, Allegra produces B3 waste. B3 waste contains materials that can pollute the environment and endanger humans and other living things. Therefore, it is necessary to plan the container and layout of the B3 Waste Temporary Storage. The data needed in this study are the types and characteristics of B3 waste, B3 waste generation, packaging planning as a B3 waste container and calculations that produce a TPS area that has sufficient capacity to temporarily accommodate B3 waste produced by Allegra. Based on the research that has been done, the results show that each waste is placed in a 200lt metal drum container, trash bag, container, and iron rack. A metal drum is placed above the container, a trash bag is placed on a pallet to avoid spillage on the floor. For waste of used rags and used accumulators/batteries, insulation is provided because they are flammable. The TPS for B3 waste is equipped with a B3 waste symbol, a 3 Kg fire extinguisher, air vents, lighting and a sink to meet the technical requirements for storing B3 waste.